Marketing mix Framework as a Tool to Enhance Women’s Business Viability in Limpopo-South Africa - Mvunabandi, Jean Damascene; Nomala, Bomi; Gadzikwa, Lawrence (International Review of Management and Marketing, 2024)
Motivated by lack of empirical research on how the marketing mix (price, place, product promotion, process, packaging, physical evidence, people, programming and partnership) directly or indirectly enhance the women’s business viability and sustainability in South Africa and elsewhere. This research empirically investigated how marketing mix can be used to enhance women’s business viability among 301 registered business owners trained in marketing and participated in the survey and answered details questions focusing on Limpopo province -South Africa. AIDA theory, diffusion of innovation theory and Marketing Mix Theory underpinned the study. Quantitative descriptive survey research strategy was adopted, Robustness analysis was entirely performed using SPSS version 28. The study’s findings were that women’s businesses in Musina and Blouberg in Limpopo province use the 10Ps. The four most used marketing strategies were, price, place promotion and product. The averagely used marketing strategies were: people, packaging, programming, physical evidence and partnership. This study contributes to the current body of knowledge and further contributes to the use of 10Ps marketing mix strategies and framework by women’s businesses. The study’s main implication is that business entities may not achieve their full financial performance potential due to little or no attention to the use of 10Ps marketing mix components and training. This study provides robust recommendations and insights into marketing practices applicable to other business entities globally.